Defending the Domestic Abuse Victim/Defendant: Why the Prison Reform Trust's Campaign to Introduce Defences for Offending Driven by Domestic Abuse Is Important - Bettinson, Vanessa (The prison journal, 2022)
This article explores the vulnerability of many UK female offenders and their experiences of domestic abuse that drives their criminality. Now that coercive control by domestic partners is more widely understood, criminal defences should take into account the impact it has upon domestic abuse victim/defendants. The Prison Reform Trust campaigned for the introduction of legal reform that would end convictions of people who committed crimes as a direct result of domestic abuse victimization. The reform has been considered during the debates on the 2021 Domestic Abuse Bill; however, the government rejected the proposal. This article considers how the application of domestic abuse defences can reduce the female prison population and discusses why legal reform is necessary.